Effectiveness of heat and mass transfer on mixed convective peristaltic motion of nanofluid with irreversibility rate. (31st August 2021) - Akbar, Y; Abbasi, F M; Zahid, U M; Shehzad, S A
Abstract: Entropy generation is one of the key features in analysis as it exhibits irreversibility of the system. Therefore, the present study investigates the entropy generation rate in a mixed convective peristaltic motion of a reactive nanofluid through an asymmetrical divergent channel with heat and mass transfer characteristics. The endorsed nanofluid model holds thermophoresis and Brownian diffusions. Mathematical modeling is configured under the effects of mixed convection, heat generation/absorption and viscous dissipation. A chemical reaction is also introduced for the description of mass transportation. The resulting system of differential equations is numerically tackled by employing the Shooting method. The findings reveal that entropy generation rises by improving the Brownian motion and thermophoresis parameters. The temperature of the nanofluid decreases due to rising buoyancy forces caused by the concentration gradient. The concentration profile increases by increasing the chemical reaction parameter. The velocity increases by enhancing the Brownian motion parameter.